Endourological Management of Iatrogenic Ureterovaginal Fistula following Obstetric and Gynecological Surgeries at Tertiary Referral Center - Upadhyay, Amit Mani; Acharya, Bigyan; Kunwar, Ashok Kumar; Tiwari, Kabir; Shrestha, Sanjesh Bhakta; Pradhan, Hema Kumari; Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To evaluate the outcome of endourological management of iatrogenic ureterovaginal fistula caused by gynecological and obstetric surgeries.Methods: This is a retrospective analysis of uretorovaginal fistula (UVF) patients who underwent UVF management with endourology technique from February 2014 to November 2019. All data were taken from fistula database. All non-obstetric/gynaecological cases and open surgical procedures leading to UVF were excluded. Diagnostic evaluation by cystoscopy and ureterorenoscopy; and use of guide wire, C-arm and DJ stent were recorded. Three to six months post-operative follow up status was also recorded.Results: There were 14 cases managed by retrograde DJ stenting. Both hysterectomy (n=10) and Cesarean Sections (n=4) were the past surgeries. Diagnosis was made by history, methylene blue test, cystoscopy, intravenous urography and CT urogram. Treatment was retrograde DJ stenting. All of them had unilateral distal ureteric injury close to vesicoureteric junction leading to ureterovaginal fistula. All were continent at the end.Conclusions: Endourological approach with retrograde DJ stenting had successful outcome in iatrogenic UVF.Keywords: double J stent, endourological technique, iatrogenic ureterovaginal fistula, ureterorenoscope.